2012
DOI: 10.1186/1742-2094-9-14
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting disease patterns in seropositive and seronegative neuromyelitis optica: A multicentre study of 175 patients

Abstract: BackgroundThe diagnostic and pathophysiological relevance of antibodies to aquaporin-4 (AQP4-Ab) in patients with neuromyelitis optica spectrum disorders (NMOSD) has been intensively studied. However, little is known so far about the clinical impact of AQP4-Ab seropositivity.ObjectiveTo analyse systematically the clinical and paraclinical features associated with NMO spectrum disorders in Caucasians in a stratified fashion according to the patients' AQP4-Ab serostatus.MethodsRetrospective study of 175 Caucasia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
692
10
44

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 658 publications
(778 citation statements)
references
References 78 publications
32
692
10
44
Order By: Relevance
“…There are probably no differences in relapse rates and clinical features between AQP4-IgG-positive patients with classical NMO and NMOSD, but AQP4-IgG-negative patients more often have bilateral ON or simultaneous ON and myelitis at disease onset than AQP4-IgG-positive patients [11,58]. While 1 study reported that a monophasic disease course is more common in AQP4-IgG-negative patients [11], this was not found in another study [58].…”
Section: Prevention Of Nmosd Attacks General Considerationsmentioning
confidence: 89%
See 3 more Smart Citations
“…There are probably no differences in relapse rates and clinical features between AQP4-IgG-positive patients with classical NMO and NMOSD, but AQP4-IgG-negative patients more often have bilateral ON or simultaneous ON and myelitis at disease onset than AQP4-IgG-positive patients [11,58]. While 1 study reported that a monophasic disease course is more common in AQP4-IgG-negative patients [11], this was not found in another study [58].…”
Section: Prevention Of Nmosd Attacks General Considerationsmentioning
confidence: 89%
“…Only every 2. to 5. NMOSD attack shows complete recovery [11,32]. In particular, bilateral ON and myelitis have low remission rates [33].…”
Section: Treatment Of Nmosd Attacksmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to the discovery of a serum immunoglobulin G antibody targeting the aquaporine-4 water channel [5,6], it was often considered a variant of multiple sclerosis (MS) as the clinical presentation of these two distinct central nervous system (CNS) diseases may overlap [1]. Indeed, patients with NMOSD are still often misdiagnosed with MS in clinical practice [7,8].…”
Section: Introductionmentioning
confidence: 99%